Effect of Fructo-oligosaccharides and Xylo-oligosaccharaide (XO) assisted biotreatment on serum lipid concentrations in mice - Bilal Saleh; Ahmed Hikmat; Khalil Khalil (College of Education for Pure Sciences, 2013)
ABSTRACT The study was investigated the ability of prebiotics in reducing the lipids concentrations in the host where used laboratory mice for this purpose. The study included giving the laboratory mice into a period (8) weeks for the food that containing fructo-oligosaccharaides (FOSs) (included two types: oligofructose and inulin) and xylo- oligosaccharaide (XO). The results were showed that FOSs of inulin type was the best compared with the other of prebiotics in reducing the harmful lipids concentrations in the serum, for reaching the reduction rates into (30%) , (11.2%) and (18%) for concentrations of triglyceride (TG) , total cholesterol (TC) and cholesterol-associated with low density lipoprotein (LDL-c) respectively. While the reduction rates were reached (15%) , (8%) and (14.5%), respectively, when used the xylo-oligosaccharaide (XO), while FOSs of oligofructose type was lowering concentrations of both total cholesterol (TC) and cholesterol associated with low density lipoprotein (LDL-c) only with reduced rates reached (8.6%) and (12.4%) respectively. The prebiotics that used in this study was no appear any effects on beneficial lipids that presented  the cholesterol-associated with high density lipoprotein (HDL-c).